Factors that influence the use of birth control by Brazilian adolescents - Diogo Fajardo Nunes Hildebrand; Andres Rodriguez Veloso (BBR: Brazilian Business Review)
The central objective of this paper is to investigate the antecedents of the use of contraceptive methods by adolescents. For this purpose, we developed and tested a theoretical model that reflects the interrelationships between assessments of self-efficacy of youths and the influences of the partner, socializing agents and adolescents’ goals in life. The results indicate that the intention to use and actual use of contraceptive methods is directly affected by perceptions of self-efficacy, life goals related to stability and education, and the respondent’s sex (boys intend to use birth control methods more than do girls). Also, the attitude of the partner in the relationship and contact with doctors are preponderant factors influencing the intention to use birth control methods. These results are relevant from the theoretical standpoint, by providing a better understanding of adolescents’ behavior, and from a practical perspective, by facilitating the development of marketing strategies and public policies to increase the use of birth control measures among young people.